Pogledi na etično obravnavo informacijsko-komunikacijske tehnologije - Pivec, Franci (Uporabna informatika (Ljubljana), 2009)
This article represents the introductory lecture at the First Ethics Forum, dedicated to the World Information Society Day 2009, and describes the efforts of IFIP and SSI for a socially critical approach towards ICT. In the foreground are the influences of new technologies on the ethical actions of people, a topic for which several theoretical approaches and patterns of practical actions have been developed in the past decades. Computer ethics is a renowned research and education "discipline" in the modern academic world, which is, from the position of professional ethics, moving into the position of "macro ethics", based on the universal value of information. This development is illustrated through the concepts of Parker, Gotterbarn, Maner, Johnson and Bynum, and characterised by Floridi''s comments. Also included is acall for a public discussion of the draft of SSI''s code of ethics.
Keywords: ethics; etika; računalništvo; computer science; informatika; information science; etični kodeks; zgodovinski pregledi